Ineficácia dos atos do falido - Gonzalez, Fernanda Cristina Villa (2010)
The fomentation of the enterprise activity is directly related to the safety given to those who participate in the economy. Thus, depending on the safety found in the enterprise relationships, there will be a large number of business transactions, and the main tool to reach that safety is clearly the law. This means that, the safer the enterprise activity is, the faster its increase will be and consequently the economic growth of a nation. The bankruptcy is an example of a law that fomentates the development of the economy, though not directly, since it establishes restrictions that offer protection and the above-mentioned safety to those involved with the economy. The possibility of declaring the inefficiency of certain acts done by the bankrupted entrepreneur, in accordance with the articles 129 to 138 (Lei nº. 11.101/05), illustrates it well. These articles prove conclusively that a protection is offered to the persons involved in the enterprise activity. In other words, the possibility of declaring that inefficiency is one of the best ways of complying with par conditio creditorum, as well as preserving the patrimony of the debtor, which is seen as a guarantee to the creditor. Not only to assure an equal treatment among creditors, but also to avoid frauds, the state should intervene in some of those acts with the aim to deprive them of efficiency in favour of the group of creditors, which is essential and contributes considerably to the stability of the relationships of this sort. However, there will be doubt about the way of reaching that inefficiency, since the law implies a different treatment for each situation. As a result, the doctrine establishes a controversy not only over the way of reaching the mentioned inefficiency, but also over the effects brought by the enforcement of the law, notably the articles 129 and 130 (Lei nº. 11.101/05)